Quench Dynamics of Neutral Atoms in Out-Equilibrium One-Dimensional Optical Lattices*Supported by Universidad Santiago de Cali Project No. 935-621115-N23, Conciencias Project Nos. 123365842816, FP44842-014-2015. (October 2018) - Leyton, V.; Arguëlles, A.; Camargo, M.
Abstract: A quantum simulator is proposed for nucleation and growth dynamics using an out-of equilibrium optical lattice. We calculate the density of neutral atoms in the lattice and we establish the connection with the Kolmogorov-Mehl-Johnson-Avrami model. Here we show that an Avrami equation can describe most of the evolution in time of the population growth in the lattice, coherence between neutral atoms leads a complex growth rate.